PELATIHAN PANDUAN HIDUP SEHAT MELALUI SENAM OLAHRAGA MASA ADAPTASI PASCA COVID 19 - Ardo Yulpiko Putra; Muarif Arhas Putra (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2023)
Sport is a basic need for every human being at this time. This is because doing sports can prevent various diseases, including: diabetes obesity, cancer, injury, and osteoporosis. In addition, exercise is also known to reduce stress and anxiety, improve sleep quality and concentration levels, and can increase self-confidence. During the current Covid-19 pandemic, exercise can be an alternative in maintaining immunity. Therefore the purpose of this community service activity is to build public awareness about the healthy living movement through sports activities. Partners in this activity are residents of the Tanjung Betung housing community, totaling 20 people. The activity method is through the transfer of knowledge and practice, while the steps are 1) counseling, 2) practice, 3) mentoring and 4) evaluation. The results of the activities include 1) partners' understanding has increased after counseling, and 2) partners can perform simple movements taught by the team. Assistance activities still need to be carried out continuously so that people are truly aware of healthy living.